Legal and Economic Harmonization of Extended Producer Responsibility (EPR) as a Strategy for Sustainable Plastic Waste Management in Southeast Asia - Alfin Dwi Novemyanto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The problem of plastic waste in Southeast Asia has become a global environmental issue that imposes economic costs and threatens marine ecosystems. UNEP (2021) and World Bank (2021) identify Indonesia, the Philippines, Vietnam, and Thailand as major contributors to marine plastic leakage. Although several countries have adopted Extended Producer Responsibility (EPR) in national policy, implementation is weak and lacks regional harmonization. This study combines normative legal research with economic impact analysis using international datasets to identify regulatory gaps and evaluate the potential benefits of harmonized EPR across ASEAN. Results indicate that fragmented legal frameworks, limited monitoring capacity, and insufficient economic incentives undermine EPR effectiveness. Economic modeling estimates annual losses exceeding USD 6 billion from plastic leakage, costs borne by communities and governments. Scenario analysis suggests that harmonized legal standards and cost-internalization via EPR could reduce leakage by up to 40% while generating employment in circular-economy sectors. The findings underscore that legal-economic integration is essential: enforceable regional rules, transparent financial flows, and producer-funded mechanisms grounded in the polluter-pays principle are needed. The study recommends an ASEAN binding framework for EPR, standardized reporting and independent audits, and blended-finance instruments to bridge investment gaps and accelerate the transition to sustainable plastic economy.